2018
DOI: 10.21608/ejh.2019.25411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the possible therapeutic role of omega-3 on ankle joint and lung in a model of rheumatoid arthritis in rats: A histological and immunohistochemical study

Abstract: Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory systemic autoimmune disease. Lung disease has been recognized as a common complication of RA. Omega-3 is an essential fatty acid with wide range of activity. Aim of the work: To investigate the possible therapeutic role of omega-3 free fatty acid on the structure of ankle joint and lung in a model of adjuvant-induced RA in rats. Materials and Methods: Thirty adult male albino rats were divided into three groups; Group I served as a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…These results were confirmed by the previous studies which showed that elevating tissue omega-3 levels can prevent and treat fine particle-induced health problems and suppress fine particle-induced pulmonary and systemic inflammation (Li et al, 2017). The therapeutic role of omega-3 was confirmed also by (Raafat et al, 2018) who found that the addition of omega-3 has an ameliorating effect on the inflammation caused due to rheumatoid arthritis on the lung tissue by H&E and (TNF-α). The anti-inflammatory effect of omega-3 was studied also by (xu et al,2011) who said that omega-3 injection effectively reduces destruction and injury in the lung of rats with severe scald.…”
Section: Discussionsupporting
confidence: 77%
“…These results were confirmed by the previous studies which showed that elevating tissue omega-3 levels can prevent and treat fine particle-induced health problems and suppress fine particle-induced pulmonary and systemic inflammation (Li et al, 2017). The therapeutic role of omega-3 was confirmed also by (Raafat et al, 2018) who found that the addition of omega-3 has an ameliorating effect on the inflammation caused due to rheumatoid arthritis on the lung tissue by H&E and (TNF-α). The anti-inflammatory effect of omega-3 was studied also by (xu et al,2011) who said that omega-3 injection effectively reduces destruction and injury in the lung of rats with severe scald.…”
Section: Discussionsupporting
confidence: 77%